Regular use of medication for musculoskeletal pain and risk of long‐term sickness absence: A prospective cohort study among the general working population. (26th August 2016) - Sundstrup, E.; Jakobsen, M.D.; Thorsen, S.V.; Andersen, L.L.
Abstract: Background: The aim was to determine the prospective association between use of pain medication – due to musculoskeletal pain in the low back, neck/shoulder and hand/wrist – and long‐term sickness absence. Methods: Cox‐regression analysis was performed to estimate the prospective association between regular use of pain medication and long‐term sickness absence (LTSA; at least 6 consecutive weeks) among 9, 544 employees from the general working population (Danish Work Environment Cohort Study 2010) and free from LTSA during 2009–2010. The fully adjusted model was controlled for age, gender, body mass index, smoking, leisure physical activity, job group, physical activity at work, psychosocial work environment, pain intensity, mental health and chronic disease. Results: In 2010, the proportion of regular pain medication users due to musculoskeletal disorders was 20.8%: 13.4% as over‐the‐counter (i.e. non‐prescription) and 7.4% as doctor prescribed. In the fully adjusted model, regular use of over‐the‐counter [HR 1.44 (95% CI 1.13–1.83)] and doctor prescribed (HR 2.18 (95% CI 1.67–2.86)) pain medication were prospectively associated with LTSA. Conclusions: Regular use of pain medication due to musculoskeletal pain is prospectively associated with LTSA even when adjusted for pain intensity. This study suggests that use of pain medication can be an important factor to be aware of in the prevention of sickness absence. Thus, regular use of pain medication – and not solely the intensity of pain – can be an early indicator that musculoskeletal pain can lead to serious consequences such as long‐term sickness absence. Significance: Use of medication due to musculoskeletal pain is prospectively associated with long‐term sickness absence even when adjusted for pain intensity. Use of pain medication can be a red flag to be aware of in the prevention of sickness absence.